The Impact of Individual Characteristics, Work Environment, and Organization Culture Against Employee Performance at PT Telkom Akses Witel Denpasar - Kadek Ryandana Wisma ANANNTA; Putu Jerry KUSUMA; Ida Bagus Agung DHARMANEGARA (Journal of Governance, Taxation and Auditing, 2023)
This research examines and analyzes the influence of individual characteristics, work environment, and organizational culture on employee performance. This research was conducted at PT. Telkom Access Witel Denpasar by arriving! The research consisted of 73 respondents using random sampling techniques. All data obtained from the questionnaire distribution is suitable for use, then analyzed using multiple linear regression hypothesis testing (t-test and f-test). The results showed that (1) Fritung (65,229)> Fable (2.74) with a significance value of F of 0.000<0.05, then Ho is rejected. This means the individual characteristic variable (X1). Work environment (X2) and organizational culture (X3) simultaneously have a positive and significant effect on employee performance (Y). The regression coefficient ß1 (individual characteristic variable) is 0.523. The regression coefficient ß2 (work environment variable) is 0.186, indicating that the better the work environment, the greater the employee performance at PT. Telkom Access Witel Denpasar. The regression coefficient B3 (organizational culture variable) is 0.267, indicating that the better the organizational culture, the greater the employee performance at PT. Telkom Access Witel Denpasar.